Parking System Application Using a Greedy Algorithm Approach - Saputri, Hanis Amalia; Syaputra, William; Charles, Charles; Irawan, Andreas Dwi; Nabiilah, Ghinaa Zain (Bina Nusantara University, 2025)
Indonesia has recently witnessed a significant increase in the number of automobiles, reaching an estimated 17.2 million units by the end of 2022, according to the Central Statistics Agency (BPS). Extensive ownership and usage of vehicles in public parking areas, including campuses, have created a high demand for parking spaces. However, challenges still exist within the parking system, such as longer search times for available parking spaces and the lack of technological regulation, leading to uncertainty. Our research focuses on addressing these issues by employing a priority-based greedy algorithm for the nearest lift, prioritizing convenience and speed. We utilize an SQL database to store parking data, leveraging its comprehensive features for efficient processing. The result of this research is a website where customers can input their license plate numbers, processed by our algorithm to generate parking tickets, granting access to designated parking areas. The algorithm works by providing parking slot locations from even-numbered floors first; when all even-numbered floors are filled, it will then allocate parking slots on odd numbered floors. The implementation of the greedy algorithm and SQL database has proven to be efficient in the context of the nearest lift in the Binus parking lot, handling a manageable amount of data and prioritizing data processing speed over achieving the optimal solution in all scenarios